Folk traditions and customs of mutual assistance as cultural determinants of the phenomenon of volunteering in the modern society - Pokhomova, Alesya A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
In the article, the author analyses the phenomenon of volunteering through the prism of a retrospective analysis of folk traditions and the custom of mutual assistance. The purpose of the work was to consider the universality of the phenomenon of assistance as a structural element of volunteering through folk traditions and customs. The article focuses on the social phenomenon of assistance and mutual assistance as an existential embodiment of the value of the Other. Tradition is considered as a value-normative anchor in an era of risk, uncertainty and event intensity. Ethnographic studies and their results indicate that for the successful functioning of the local community in a traditional society, the custom of mutual assistance in various aspects of everyday life was followed. Folk customs of mutual assistance performed the function of social protection for the most vulnerable categories of people at the early stages of human history. Later, the values of caring for one’s neighbour and helping those in need were internalised in the corpus of religious ideology, taking the forms of charity, alms, etc. With the strengthening of rationalisation, the formation of a secular state, state institutions in the field of social protection of the population appeared, and the phenomenon of social assistance and mutual assistance took the form of volunteering in the context of civil society.
Keywords: volunteer activity; traditions; mutual assistance; culture; folk customs; trust; rationality; local communities